2018
DOI: 10.1016/j.humpath.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating breast carcinoma with signet ring features from gastrointestinal signet ring carcinoma: assessment of immunohistochemical markers

Abstract: Signet ring morphology is recognized throughout the gastrointestinal tract. However, this pattern may be observed in other primary sites giving rise to diagnostic challenges in the work-up of metastases. Relatively newer immunohistochemical markers have not been evaluated in this context. We assessed expression patterns of several common immunohistochemical markers in tumors with Signet ring morphology to delineate a pragmatic approach to this differential diagnosis. Primary breast and gastrointestinal carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…In this work, GATA3 exhibited the strongest qualities to differentiate between the groups with high sensitivity varying from 88 to 92% and specificity varying from 95.8–100%. These results are in agreement with findings from prior studies on primary breast tumors [5, 19, 20].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this work, GATA3 exhibited the strongest qualities to differentiate between the groups with high sensitivity varying from 88 to 92% and specificity varying from 95.8–100%. These results are in agreement with findings from prior studies on primary breast tumors [5, 19, 20].…”
Section: Discussionsupporting
confidence: 93%
“…Another study by Hui et al [20], demonstrated that all PDGC were negative for GATA3 and recommended the utility of this marker for the distinction from lobular breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31] In a study with 40 breast adenocarcinomas of exclusively mucinous phenotype undertaken by de Andrade Natal et al, 29 all cases were negative for CDX2 expression. Additionally, in a cohort of 33 breast and 50 gastrointestinal (upper and lower) signet ring cell adenocarcinomas reported by Hui et al, 30 CDX2 staining was 100% specific for tumors of gastrointestinal origin. Keeping in line with these data, our CDX2 false-positive rate was 0% in our purely mucinous cohort of breast adenocarcinomas regardless of H-score (Table 2) although any SATB2 expression was observed in 16.1% of cases.…”
Section: Mucinous Carcinomas Of the Lower Gastrointestinal Tractmentioning
confidence: 99%
“…It has 100% positivity in lobular breast carcinoma and 96% positivity in ductal carcinoma of the breast [3] . In primary gastric carcinoma it is positive in only 5% (in well-differentiated adenocarcinomas, with no reported cases in carcinomas with poorly cohesive cells, such as signet ring carcinomas) [13] .…”
Section: Discussionmentioning
confidence: 99%